2022
DOI: 10.1167/tvst.11.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genes of Staphylococcus aureus Associated With Keratitis, Conjunctivitis, and Contact Lens–Associated Inflammation

Abstract: Purpose Staphylococcus aureus , cause a range of ocular diseases in humans, including noninfectious corneal infiltrative events (niCIE), infectious conjunctivitis and sight threatening microbial keratitis (MK). This study aimed to determine the possession of known virulence genes of S. aureus associated with MK and conjunctivitis, in strains isolated from these conditions and niCIE. Methods Sixty-three S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…The current study’s genotypic data shows that infectious isolates from USA harbored more antimicrobial resistance genes (ARGs) compared to Australian isolates, which supports the phenotypic data of the previous study. Similarly, PCR results for a subset of 12 known virulence genes had previously reported that genes involved in evasion and invasion ( hlg and hld ) were more commonly found in infectious isolates than niCIE [ 13 ]. The current study results for hld are consistent with the previous report [ 13 ].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…The current study’s genotypic data shows that infectious isolates from USA harbored more antimicrobial resistance genes (ARGs) compared to Australian isolates, which supports the phenotypic data of the previous study. Similarly, PCR results for a subset of 12 known virulence genes had previously reported that genes involved in evasion and invasion ( hlg and hld ) were more commonly found in infectious isolates than niCIE [ 13 ]. The current study results for hld are consistent with the previous report [ 13 ].…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, PCR results for a subset of 12 known virulence genes had previously reported that genes involved in evasion and invasion ( hlg and hld ) were more commonly found in infectious isolates than niCIE [ 13 ]. The current study results for hld are consistent with the previous report [ 13 ]. However, hlg which was more common in infectious strains than niCIE strains in the previous study [ 13 ] was found in ≥96% of all S. aureus isolates in the current study.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations